Information Systems in Healthcare – State and Steps towards Sustainability - Lenz, R. (Yearbook of Medical Informatics, 2009)
Objectives To identify core challenges and first steps on the way to sustainable information systems in healthcare.Methods Recent articles on healthcare information technology and related articles from Medical Informatics and Computer Science were reviewed and analyzed. Core challenges that couldn’t be solved over the years are identified.Results The two core problem areas are process integration, meaning to effectively embed IT-systems into routine workflows, and systems integration, meaning to reduce the effort for interconnecting independently developed IT-components. Standards for systems integration have improved a lot, but their usefulness is limited where system evolution is needed.Conclusions Sustainable Healthcare Information Systems should be based on system architectures that support system evolution and avoid costly system replacements every five to ten years. Some basic principles for the design of such systems are separation of concerns, loose coupling, deferred systems design, and service oriented architectures.
Keywords: Information system; systems Iitegration; medical informatics applications